On the characterization of NaDEHP/n-heptane nonaqueous reverse micelles: the effect of the polar solvent. Issue 10 (16th February 2015) - Quintana, Silvina S.; Dario Falcone, R.; Silber, Juana J.; Moyano, Fernando; Mariano Correa, N.
Abstract : Schematic representation of different interfaces in the novel nonaqueous NaDEHP/ n -heptane reverse micelle. Abstract : The behavior of two polar solvents, ethylene glycol (EG) and dimethylformamide (DMF), entrapped in sodium bis-(2-ethylhexyl) phosphate (NaDEHP)/ n -heptane reverse micelles (RMs) was investigated using dynamic light scattering (DLS), molecular probe absorption and FT-IR spectroscopy. DLS results reveal the formation of RMs containing EG and DMF as a polar component. To the best of our knowledge this is the first report where both polar solvents are entrapped by the NaDEHP surfactant to effectively create RMs. We use the solvatochromism behavior of the molecular probe, 1-methyl-8-oxyquinolinum betaine (QB), and FT-IR spectroscopy to investigate the physicochemical properties of the non-aqueous RMs. Our results demonstrate that the NaDEHP surfactant interacts through hydrogen bonds with EG at the EG/NaDEHP interface and this interaction is responsible for destroying the bulk structure of pure solvent EG when entrapped in NaDEHP RMs. On the other hand, when DMF is incorporated inside the RMs the bulk structure of DMF is destroyed upon encapsulation by the Na–DMF interaction at the DMF/NaDEHP interface. Our results are completely different than the one observed for DMF/ n -heptane/AOT. Our results show how the physicochemical properties, such as micropolarity, microviscosity and hydrogen bond interaction, of nonaqueous NaDEHP/ n -heptane RMs interfaces can be dramatically changed by simply using different non-aqueous polar solvents. Thus, these results can be very useful to employ these novel RMs as nanoreactors since the dimensions of the RMs are around 10 to 20 nm.